Imbalance, inequality, equity, and adjustment in Pay-As-You-Go pension systems in developing countries: An empirical analysis with data from Brazil - Ajax Moreira; Miguel Nathan Foguel; Sérgio Guimar\~aes Ferreira (Institute for Applied Economic Research (ipea), 2022)
Using an empirical age-period-cohort model we analyze the effects of different Pay-As-You-Go (PAYG) public pension systems on financial imbalance, on inequality in permanent income, and on the rate of return of social security assets of heterogeneous agents in terms of gender and education. Apart from this heterogeneity, we include some aspects that are particularly relevant for developing countries such as the existence of labor informality (seen as non-contribution to the pension system) and of an old-age, social benefit granted to those that are not eligible for regular retirement. We consider several types of PAYG structures, including the defined benefit (DB) system, the notional defined contribution (DC) system, and a new mixed system that combines components of the two previous ones. Results are obtained both for a context in which there is no financial equilibrium and for a context with financial balance. In this last case, we use distinct schemes of partition of the imbalance between active and inactive generations, with one of the schemes inspired in the present German system where the contribution of the latter group is based on changes in the dependency ratio and in the wages net of contributions. The analysis for the inequality measure and the rate of return is conducted both for intra and intergenerational perspectives. The results of our simulations show that the mixed system herein proposed represents a compromise between the DB and DC systems. Within the context with financial balance, the German scheme tends to exhibit the highest rates of return and the highest horizontal equity in returns.
Keywords: H43; H55; H62; 330; public pension systems; financial imbalance; inequality; simulations